An Act to Provide for the Appointment of Inspectors and Regulating the Manufacture of Gunpowder, 1820 N.H. Laws 907, ch. 24, §§ 1-9 - (:unkn) unknown (General Publisher, 1820)
Authorized the creation of "inspector of gunpowder" for public powder magazines and powder manufactories. Required gun powder manufactured in the state to be composed of certain qty/quality of materials. Authorized inspection of gunpowder. Bans sale of gunpowder not up to standards.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER